Ancient Chinese Thought, Modern Chinese Power - Yan Xuetong (Princeton University Press, 2013)
During a conversation in Beijing in 2008, Dr. Henry Kissinger told me he believed thatâ€”when China became a strong world powerâ€” the Chinese government would adopt ancient Chinese philosophy rather than Marxism or liberalism to guide its foreign policy. He also believed that people outside of China would be eager to learn about these matters. His two predictions proved to be correct after just three years. In September of 2011, only six months after this book was published, the Chinese government published its white paper on foreign policy called Chinaâ€™s Peaceful Development. The white paper clearly stated that the Chinese government based its foreign policy on the fine tradition of Chinese culture, and that â€œPeaceful development carries forward Chinese historical and cultural tradition.â€1 Of course, I do not mean to imply that my book itself brought about a new foreign policy; rather, it aims to systematize thinking about what Chinaâ€™s foreign policy ought to look like, and to set standards to evaluate progress and regress in foreign policy. I hope that my book can help to steer the wave in a direction that is both moral and realistic. By the end of 2012, the book seems to have struck a chord in different disciplines and in different countries. The photo of United States Vice President Joe Biden holding this book in Chengdu Airport, China, in August 2011 reflects the bookâ€™s attractiveness to politicians. The New York Times commissioned and published my article linking the core idea of this book with China-United States relations in late 2011, and it turned out to be one of the top ten most emailed articles the day it appeared.2 Finally, the World Economic Forumâ€™s annual 2012 meeting in Davos held a special session on this book.